Identification of novel CDK2 inhibitors by a multistage virtual screening method based on SVM, pharmacophore and docking model. (1st January 2020) - Liang, Jing-Wei; Wang, Ming-Yang; Wang, Shan; Li, Shi-Long; Li, Wan-Qiu; Meng, Fan-Hao
Abstract: Cyclin-dependent kinase 2 (CDK2) is the family of Ser/Thr protein kinases that has emerged as a highly selective with low toxic cancer therapy target. A multistage virtual screening method combined by SVM, protein-ligand interaction fingerprints (PLIF) pharmacophore and docking was utilised for screening the CDK2 inhibitors. The evaluation of the validation set indicated that this method can be used to screen large chemical databases because it has a high hit-rate and enrichment factor (80.1% and 332.83 respectively). Six compounds were screened out from NCI, Enamine and Pubchem database. After molecular dynamics and binding free energy calculation, two compounds had great potential as novel CDK2 inhibitors and they also showed selective inhibition against CDK2 in the kinase activity assay.